2020
DOI: 10.3390/ijerph17176255
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Mental Health in the Family: The Influence of Emotional Intelligence Perceived by Parents and Children

Abstract: Introduction: The relevant scientific literature has confirmed the relationship between emotional intelligence (EI) and mental health. In addition, previous studies have underlined the importance of perceived EI between family members in the construction of one’s own EI. Adolescence is considered to be a crucial stage in identity construction and a time when mental health is vulnerable. Objectives: To analyze the mediating role of self-reported EI on mental health of adolescents and young adults still living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 55 publications
0
18
0
7
Order By: Relevance
“…Previous scientific literature supports the same relationship between family function and social support [ 49 ], and between social support and adolescent adjustment [ 51 , 52 , 53 , 54 ]. Thus, as demonstrated by Sánchez-Nuñez et al [ 74 ], parents exert an extremely strong influence on emotional development, forging the image of their children with respect to their own emotional skills by emotional socialization, and are essential in the psychosocial adjustment of adolescents in different environments [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous scientific literature supports the same relationship between family function and social support [ 49 ], and between social support and adolescent adjustment [ 51 , 52 , 53 , 54 ]. Thus, as demonstrated by Sánchez-Nuñez et al [ 74 ], parents exert an extremely strong influence on emotional development, forging the image of their children with respect to their own emotional skills by emotional socialization, and are essential in the psychosocial adjustment of adolescents in different environments [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed the importance of EI to mental and physical health [ 41 , 42 ]). The present study aimed to analyse how EI interacts with disease management.…”
Section: Discussionmentioning
confidence: 99%
“…The scale is made up of three factors or subscales: attention to feelings, emotional clarity and mood repair. The Cronbach's α has reported internal consistencies for attention 0.88, clarity 0.89 and repair 0.86 (Sánchez‐Núñez et al, 2020).…”
Section: Methodsmentioning
confidence: 99%